2002
DOI: 10.3354/meps240001
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling nitrous oxide at the microbial community and estuarine scale

Abstract: This paper examines the effect of oxygen on nitrous oxide (N 2 O) concentrations in estuarine waters. N 2 O has been measured year-round in the Schelde estuary, a high-nitrogen, lowoxygen macrotidal system. N 2 O concentrations were above atmospheric equilibrium levels indicating that this estuary represents a source to the atmosphere. The distribution of N 2 O showed consistent and systematic relationships with distribution patterns of ammonium, oxygen, nitrite and nitrification activities. A controlled labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 41 publications
2
32
1
Order By: Relevance
“…Our results show that below suboxic conditions, this process takes place -as deduced from global models (Nevison et al 2003) or through direct measurements on waters of the Indian Shelf (Naqvi et al 2000), the Baltic Sea (Brettar & Rheinheimer 1992), suboxic estuaries (De Bie et al 2002), and marine bacteria cultures (Goreau et al 1980, Bonin et al 1989, De Bie et al 2002where the N 2 O produced from NH 4 + oxidation increased within microenvironments having low O 2 and NH 4 + availability (Avrahami et al 2002). In addition to this, potential nitrification rates (0.091 to 0.62 µM d -1 ) have been measurable in the OMZ core off Iquique (V. Molina et al unpubl.…”
Section: The Omz In the Eastern South Pacificmentioning
confidence: 56%
“…Our results show that below suboxic conditions, this process takes place -as deduced from global models (Nevison et al 2003) or through direct measurements on waters of the Indian Shelf (Naqvi et al 2000), the Baltic Sea (Brettar & Rheinheimer 1992), suboxic estuaries (De Bie et al 2002), and marine bacteria cultures (Goreau et al 1980, Bonin et al 1989, De Bie et al 2002where the N 2 O produced from NH 4 + oxidation increased within microenvironments having low O 2 and NH 4 + availability (Avrahami et al 2002). In addition to this, potential nitrification rates (0.091 to 0.62 µM d -1 ) have been measurable in the OMZ core off Iquique (V. Molina et al unpubl.…”
Section: The Omz In the Eastern South Pacificmentioning
confidence: 56%
“…CO 2 , CH 4 , and N 2 O) accumulated in hypoxic waters beneath the stratified surface layer can be released into the atmosphere, potentially having a considerable feedback to climate change. It has been suggested that coastal hypoxic areas are important contributors to the atmospheric inventory of long-lived greenhouse gases (Naqvi et al, 2000De Bie et al, 2002;Zhang et al, 2008). Coastal hypoxia can also influence the oceanic inventory of dissolved oxygen, nutrients and other greenhouse gases through exchange with open ocean waters and down-welling.…”
Section: Scaling-up the Results From Coastal Hypoxia Studiesmentioning
confidence: 99%
“…In the few coastal hypoxic systems that are mostly anthropogenically formed and have been sampled for N 2 O, substantial enhancement of N 2 O concentration has been reported. Coastal hypoxia due to eutrophication are hot spots for N 2 O release not only because of low oxygen conditions, but also because of high nitrogen loadings and fluxes (De Bie et al, 2002). For instance, off the mouth of Changjiang in the East China Sea, concentrations of N 2 O in the hypoxic layer (i.e.…”
Section: Feed-back To the Earth Systemmentioning
confidence: 99%
“…In the water column with low oxygen concentrations and in sediments or inside suspended particles, nitrification and denitrification can occur simultaneously and are often closely coupled (Seitzinger, 1988;Ward et al, 1989;Capone, 1991;Middelburg et al, 1996;Barnes and Owens, 1998;Naqvi et al, 1998;Robinson et al, 1998;Usui et al, 2001;Nevison et al, 2003;Codispoti et al, 2005;Bange, 2008). The yield of N 2 O from both processes is highly dependent on the concentration of dissolved oxygen (Goreau et al, 1980;de Bie et al, 2002;Naqvi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%